(untitled) (International Journal of Engineering and Computer Science, 2014)
Nowadays social networking has become a requisite and obsession rather than a service. In this ever progressive system, we propose a tweet suggestion system that enhances the basic features of the prevailing tweet structure. In this paper we explore the framework of mining multiple hashtags from tweets in the data repository and suggesting the tweets to the user based on their previous tweets. The algorithm employed here is the Apriori algorithm that mines the frequent data item-set and presents us with the hashtags required for the suggestion.